Water Pipeline Monitoring System Using Flow Sensor Based on the Internet of Things - Dedy Wahyu Herdiyanto; Triwahju Hardianto; Dimas Ardiansyah; Immawan Wicaksono; Widya Cahyadi; Catur Suko Sarwono (Fakultas Teknik, Universitas Jember, 2023)
Pipe leakage is one of the most common problems in agriculture. Especially if the agricultural land is quite large, it will be challenging to determine the location if a leak occurs. Active sensors are not recommended because they do not follow the green computing concept (energy-efficient computing). This study is proposed to use a passive type sensor that is more energy efficient. This study will use a water flow sensor placed at several points in the irrigation pipe network. The water flow sensor was chosen because this sensor works passively and is very accurate in detecting changes in water flow, especially in flowing water. The sensor reading results will be sent using the Internet of Things with a Wi-Fi connection. The collected data results are processed on the server and displayed in an interface that makes it easy for users to monitor water flow through smartphones. The results of the tests that have been carried out show that the designed system has worked as expected. The system can detect the location of the leaking pipe flow and indicate the leaking pipe.